Pengujian Kandungan Residu Pestisida Pada Tanaman Sayuran Di Kabupaten Badung Dengan Kartu Pendeteksi Pestisida (Pesticide Detection Cards) Dan Gas Chromatography Mass Spectrophotometry - Duniaji, Agus Slamet; Suter, I Ketut (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 4 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i04.p19, 2021)
Pesticides are chemical substances used to control various pests and diseases. In the field, synthetic pesticides are widely used and their use is not controlled and exceeds the permitted threshold according to the Minister of Agriculture No: 88 Permentan/PP.340/12/2011. The purpose of this study was to determine the content of pesticide residues in vegetables cultivated in Badung district. A total of 16 types of vegetables with 32 samples were tested for pesticide residues of organophosphorus and organochlorine groups (Diazinon, chlorphyrifos and Profenopos) on vegetable crops in Badung district. Qualitative testing was carried out with pesticide detection cards (Pesticide Detection Cards) and then samples contaminated with pesticides were continued by testing using Gas Chromatography Mass Spectrophotometry (GC MS) / The test results showed that as many as 30 samples of vegetables (93.75%) did not contain diazinon and as many as 2 samples (6.25%) containing diazinon, namely chinese cabbagge sample 1 of 0.015 ppm and chinese cabbagge of sample 2 of 0.024 ppm. A total of 29 samples of vegetables (90.63%) did not contain much chlorphyrifos and as many as 3 samples (9.37%) contained chlorphyrifos pesticide residues. A total of 30 samples (93.75%) contained profenofos and 2 samples of vegetables (6.25%) contained profenofos pesticide residues in the mustard greens sample 1 and chicory sample 2 were 0.048 ppm and 0.029 ppm, respectively. According to PERMENTAN No: 88 /Permentan/PP.340/12/2011, from the results of this test, all samples were below the Maximum Residue Limit (BMR) for pesticide diazinon, chlorphyrifos and profenofos